Development patterns of the dynamic elastic modulus of saturated coral sand under different drainage conditions - Zhou, Ruirong; Huo, Zhilei; Liu, Qifei; Yu, Qingquan; Wu, Qi (Frontiers in Marine Science, 2024)
Long-term cyclic loading can have a significant effect on the modulus of sand, and the influence on saturated coral sand has yet to be established. In this paper, the significant influence of non-plastic fines content (FC) and relative density (Dr) on dynamic elastic modulus (E) of saturated coral sand has been evaluated by a series of cyclic triaxial drainage tests. The results show that the dynamic elastic modulus increases rapidly at the beginning of loading; then the growth slows down and finally stabilizes. In general, the development of E is influenced collectively by FC, Dr and cyclic stress ratio (CSR). The initial dynamic elastic modulus Ed-1 and steady-state dynamic elastic modulus Ed-s increase with the increase of Dr, and decrease as FC increases. The linear fitting equations are given by introducing the equivalent skeleton void ratio esk*. Furthermore, the relative dynamic elastic modulus Er is defined as the ratio of Ed-N to Ed-s, and the prediction equation for Er was developed to provide a basis for the engineering mechanical parameters of coral sands under long-term loads.